PERBEDAAN KADAR GLUKOSA DARAH PUASA FASE FOLIKULAR DAN FASE LUTEAL MENSTRUASI PADA SISWI SMK ASSA’ADAH - Roudhotul Mazidah; Muhammad Sungging Pradana; Christina Destri; Siti Nur Husnul Yusmiati (Jurnal SainHealth, 2022)
Menstrual disorders are important indicators that indicate impaired reproductive system function that can be associated with an increased risk of various diseases such as uterine cancer, breast cancer, infertility and diabetes mellitus (DM). This is due to the presence of estrogen receptors on pancreatic cells which will increase insulin release and will be influenced by hormonal changes in the menstrual phase. Blood glucose or blood sugar is the main nutrient used for cell metabolism and energy supply in the body, and regulates and maintains glucose within normal limits.This study aims to determine the differences in fasting blood glucose examination in the follicular phase and the luteal phase in menstruating women. This type of research is descriptive with quantitative laboratory analysis techniques, namely calculating fasting blood glucose levels. The material used for this test was the blood of patients as many as 10 samples for the follicular phase and the luteal phase. The results obtained in the follicular phase with results that were not much different from normal values, while in the luteal phase the results slightly increased from the normal value of 70-110 mg/dL and the results obtained a difference in percentage with the results of 13%.